2019
DOI: 10.1177/0269216319834225
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Palliative Care: A qualitative study evaluating the perspectives of pregnancy counselors

Abstract: Background: A prenatal diagnosis of a life-limiting disease raises complex ethical, emotional, and medical issues. Studies suggest that 40%–85% of parents decide to continue the pregnancy if given the option of Perinatal Palliative Care. However, structured Perinatal Palliative Care programs are missing in many European countries. In Germany, parents have the right to free psychosocial support from pregnancy counseling services after the prenatal diagnosis of a life-limiting disease. Aim: We aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 49 publications
2
25
0
2
Order By: Relevance
“…For the latter, a national structured perinatal palliative care program would be the optimum setup. However, such programs are missing in many European countries [22]. Regarding TOP, it has been shown that it is more often chosen in situations involving high-risk CHD and complex extracardiac malformations [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the latter, a national structured perinatal palliative care program would be the optimum setup. However, such programs are missing in many European countries [22]. Regarding TOP, it has been shown that it is more often chosen in situations involving high-risk CHD and complex extracardiac malformations [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While research from the United States, Australia and Europe has recommended structured perinatal palliative care programmes for families who choose to continue a pregnancy with foetal anomalies (Cortezzo et al, 2020; Flaig et al, 2019; Guimarães et al, 2019; O’Donoghue, 2019; Weeks et al, 2020), following TOPFA many parents have reported feeling inadequately supported. Specifically, concerns have included a lack of relevant information to inform decision‐making, inconsistent levels of support during the termination and in follow‐up, and perceived negative attitudes from healthcare professionals (Hodgson et al, 2016; Pitt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the weight and impact that LTOP decisions have on prospective parents, it is essential that decisions are recognized as the major life crises that they are that, as a result, require more time and space for support from the healthcare team. However, time pressure and decisional loneliness might also be the result of fragmentation of care and the delay that decentralized care can cause, which might lead to situations where little time is left for a well-informed decisional process (Flaig et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A more structured implementation of some of the principles of perinatal palliative care might help address this limitation and further complement and integrate the supportive actions of perinatal specialists (Denney-Koelsch & Côt e-Arsenault, 2020; Flaig et al, 2019). Although there is some debate about the role of perinatal palliative care in situations where women or couples consider terminating their pregnancy (Lefkowits & Solomon, 2016;Rusalen et al, 2019), it goes without saying that involved families should receive well-established longitudinal care (including bereavement support) and time to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%